Semiotic Analysis of Cigarette Advertising: A Case Study in South Tangerang - Hartono, Hartono (Universitas Airlangga, 2024)
Cigarette advertisements are products that have restrictions and regulations in their promotion. With that, cigarette advertisements utilize creativity that has connotations to avoid bans that could lead to controversy. Through Roland Barthes' semiotic theory regarding the meanings of denotation and connotation, as well as myths, the connotations found in cigarette advertisements become a complex and interesting topic to discuss. By using a descriptive qualitative research method through the collection of primary and secondary data via observation and documentation. The results of the analysis through denotation, connotation, and myth are as follows: first, the denotation in advertisements in the form of illustrated images is a literal description that does not require deeper interpretation, while the connotation in advertisements in the form of illustrated images and text represents a secondary meaning that goes beyond denotation, which requires deeper interpretation. Second, the myth in advertisements that consist of illustrations and text is the result of a combination of meanings from the two associative terms, namely denotation and connotation, which are then agreed upon and believed.